Régimen especial y su repercusión en cambio al mype tributario de la empresa Sivigel Seguridad Integral S.A.C, distrito Trujillo- 2018 - Santillan Toro, Homer James (2020)
The objective of the study of the present investigation is to determine the repercussion of the change of the special regime to the tax MYPE of the company Sivigel Seguridad Integral S.A.C of the district of Trujillo period 2018. Establishing how the MYPE tax regime is more advantageous than the special regime in terms of determining the company's income tax calculation. The population is made up of the company Sivigel Seguridad Integral S.A.C. and the sample is made up of the company's information corresponding to the year 2018. For the development of this research, the Inductive-Deductive method was used, in addition to a non-experimental design of cross section; surveys were applied through the use of a questionnaire guide, and the financial, economic and fiscal information of the company was also analyzed; The main result is that the change to the tax MYPE regime is favorable in the monthly and annual payment on account due to the fact that it allows the deduction of expenses, which is reflected in a lower payment of income tax, so it is concluded that there is an economic advantage in favor of the tax MYPE.